A Review Of Interventional Radiology Services In Saudi Arabia: Growth, Accessibility, And Role In Minimally Invasive Treatment Pathways (The Review of Diabetic Studies, 2024)
Interventional radiology (IR) has become one of the pillars of minimally invasive healthcare and it involves the use of image-guided procedures to diagnose and treat diseases that have a shorter recovery period and less complication. In Saudi Arabia, ir services have increased at a high rate under the vision 2030 due to the infrastructure developments and increasing burdens of chronic diseases. This is a critical review on the literature published in 2020-2025 on the expansion of IR (e.g., market growth of USD 552.6 million to USD 920 million at a 5.83% prove of CAGR), its accessibility issues (e.g., urban bias, low referral rates of 22.4% among primary care physicians), and contribution to minimally invasive pathways (e.g., angioplasty, embolization, biopsies that can reduce surgical requirements). Based on 35 articles, it is found that student awareness is variable (48-82%), physician knowledge gaps are limited (only 29.6% of rating high), and teleradiology is contributing to the workflow efficiency (103,730 scans in 10 years and with a turnaround of 19.48 hours). The barriers are educational gaps and rural inequalities. Tables are used to summarize the studies, tables are used to indicate the patterns of growth, levels of awareness and pattern of referrals. The argument attacks evidence prejudices in favor of urban centers and demand integration of the curriculum. It is suggested to use standardized training, develop telemedicine, and modify the policies to provide equal access. The combination of IR in oncology, vascular, and trauma care will deliver more improved results, which are in line with the healthcare transformation in Saudi.